(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Steel structural elements are sensitive to elevated temperatures, while timber elements have good thermal insulation properties. Timber material can fulfill the role of fire protection of steel members. The effect of the protection is demonstrated on an experiment with three beams with different levels of the protection, placed into a horizontal furnace. The experimental task was also numerically analysed with standard computational approach given by the Eurocode [1, 2], which leads to an interesting comparison, as the calculation is supposed to provide higher temperatures and larger deformations compared to the experimental data.